Estudio de factibilidad para la implementación de una empresa dedicada al almacenamiento, distribución y tratamiento de alimentos perecibles en el cantón Jama provincia de Manabí - Plua Pincay, Jennifer Lisbeth (2018)
The main objective of this research is to carry out a feasibility study for the creation of a collection center for the efficient distribution of the food received by donations from the inhabitants of the El Matal Parish in the Jama Canton, as well as the use adequate food waste not suitable for human consumption, to be transformed into organic fertilizer and subsequently marketed. The consequences of the earthquake that Ecuador suffered in 2016 were devastating, until this date many affected communities and cantons receive food as a donation, such is the case of El Matal Parish, Jama Canton, however, donations do not they are efficiently distributed and organized, resulting in large amounts of losses in food unfit for human consumption, and this is coupled with the non-use of waste. Given this situation, it is of interest for the researcher to propose the creation of a collection center where the aforementioned activities are carried out…………